Sural nerve graft in peripheral nerve injuries: systematic review of the literature and analysis of the donor site complications - Saracco, Michela; Pataia, Elisabetta; Maccauro, Giulio (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Traumatic injuries of the peripheral nerves commonly occur in the workplace or in traffic accidents and affect young people, mostly males. When possible, acute repair should always be performed. But this is not always possible and it is necessary to use autologous graft with sural nerve. The purpose of this review is to illustrate the effectiveness of the sural graft for the management of these lesions. We also evaluated complications related to the donor site. Methods: This systematic review was conducted according to the PRISMA guidelines. After the full-text analysis, 8 articles were included in the review. We extracted data on the number of patients, gender, mean age, damaged nerve, time between trauma and surgery, mean follow-up, nerve gap, percentage of patients who reported scores of S3 or higher and M3 or higher. The second part of the review analyzed complications related to the donor site. Results: The sural graft was effective in managing nerve damage in both upper and lower limbs, obtaining percentages close to 50% for the restoration of sensitivity and function higher than S3 and M3, respectively. 92.6% of patients complained of sensory deficit at the donor site, followed by allodynia reported by 36 patients (26.7%) and chronic pain only in 9.6% of cases. Conclusions: The sural nerve graft effectively manages peripheral nerve injuries, with acceptable outcomes at the donor site. We also aim to highlight any existing gaps in knowledge and propose directions for future research.